Intersemiotic Explication of Non-Verbals in Amateur Subtitling - Georgios Damaskinidis (Syn-Thèses, 2019)
Generally, amateur subtitling is governed by norms that are considerably different to professional subtitling. For example, amateur subtitles can grant much more attention to aspects of the film that do not use verbal language to address the audience, such as image, space, colour, sound and movement. Therefore, comparing the consideration given to these aspects in professional and non-professional subtitles seems quite promising. This also involves a brief introduction of the distinction between funsubbing and fansubbing. Evidence from previous studies suggests that the current semiotic status of interlingual subtitling does not provide a solid basis for an integrated approach to the peculiarities of audiovisual translation. This research approaches explicitation from an intersemiotic point of view to analyse the effect of non-verbal semiotic elements on the interlingual subtitling of the film Flawless by Greek funsubbers. First, I identify selected dialogues which demonstrate significant differences between funsubbing and professional subtitling in terms of wording and grammar. Second, I refer specifically to the way non-verbal semiotic elements seem to have affected the interlingual translation of the identified Greek funsubbed dialogues. Third, I relate these intersemiotic relations to the general assumptions made about the way funsubbers translate the dialogue from a socio-semiotic perspective. Ultimately, a semiotic description of non-verbal signifying processes is offered that allows for a creative reconceptualization of amateur subtitling in intersemiotic terms.